THE EFFECT OF LIQUIDITY, RETURN ON INVESTMENT, ASSET TURNOVER, OPPORTUNITY GROWTH OF COMPANY PROFITABILITY IN THE INDUSTRIAL SECTOR FOOD AND BEVERAGE SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2018-2021 - Alya Syahla; Mohamad Trio Febriyantoro; Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study is to determine the effect of liquidity, return on investment, asset turnover, growth opportunities on company profitability in the food and beverage industry sector which is listed on the Indonesia Stock Exchange for the 2018-2021 period. The type of research used in empirical studies is quantitative research which has a positivistic paradigm. The population in this study includes all food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The samples were selected using the Probability Sampling approach and obtained a total sample of 26 companies. The data analysis technique used in this study is panel data regression analysis, using eviews software. It was found that the fixed effect is the best model because it has the largest R square value. The results showed that liquidity as described by the current ratio has a negative and significant effect on company profitability, Return On Investment affect the profitability of companies in the sector food and beverage positively and not significantly. Asset turn over (TATO) affect the company's profitability infood and beverage negatively and not significantly. Growth Rateaffect the profitability of the company on food and beverage negatively but not significantly. Profitability can be explained by the current ratio, return on investment, TATO, and a growth rate of 60.5% while 39.5% is influenced by other variables outside this study.